Early Christian manuscripts: examples of applied method and approach - Kraus, Thomas J.; Nicklas, Tobias (Brill eBook titles, 2010)
Reconstructing fragmentary manuscripts : chances and limitations / Thomas J. Kraus -- Hunting for Origen in unidentified papyri : the case of P.Egerton 2 (= inv. 3) / Rachel Yuen-Collingridge -- Papyrus oxyrhynchus X 1224 / Paul Foster -- Is P.Oxy.XLII 3057 the earliest Christian letter? / Lincoln H. Blumell -- [...] (P.Yale I 3) and the question of its function / John Granger Cook -- The reuse of Christian texts : P.Macquarie inv. 360 + P.Mil.Vogl.inv. 1224 ([...]) and P.Oxy. X 1229 ([...]) / Don Barker -- Papyri, parchments, ostraca, and tablets written with biblical texts in Greek and used as amulets : a preliminary list / Theodore de Bruyn -- The Egyptian Hermas : the shepherd in Egypt before Constantine / Malcolm Choat and Rachel Yuen-Collingridge -- The Babatha archive, the Egyptian papyri and their implications for study of the Greek New Testament / Stanley E. Porter